2010
DOI: 10.1111/j.1365-3156.2010.02560.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative epidemiological study of hepatitis B and hepatitis D virus infections in Yanomami and Piaroa Amerindians of Amazonas State, Venezuela

Abstract: Summaryobjectives To report the prevalences of hepatitis B (HBV) and hepatitis D (HDV) infections in remote and more accessible Yanomami and Piaroa Venezuelan Amazonian Amerindian populations; to estimate incidence per susceptible.methods Clinico-epidemiological evaluation was carried out in 9 Piaroa villages. Blood samples were tested for HBV core antibody (anti-HBc), surface antigen (HBsAg) and HDV antibody (anti-HDV).Results were analysed using logistic regression, and estimates made of HBV forces of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 21 publications
1
32
0
7
Order By: Relevance
“…As described previously, this community showed a lower rate of acquisition of anti-HBc antibodies (1.4% in individuals less than 15 years old), compared to the Yanomami for example (38% in individuals less than 15 years old) [2]. The lower prevalence of HBV exposure and infection in this Amerindian community may be due to its geographic location, since being located near the main urban centre of the state, it is closer to health services.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…As described previously, this community showed a lower rate of acquisition of anti-HBc antibodies (1.4% in individuals less than 15 years old), compared to the Yanomami for example (38% in individuals less than 15 years old) [2]. The lower prevalence of HBV exposure and infection in this Amerindian community may be due to its geographic location, since being located near the main urban centre of the state, it is closer to health services.…”
Section: Discussionsupporting
confidence: 49%
“…Total anticore antibodies (anti-HBc) prevalence was 17% (26/150) in this group and 31% (25/80) in individuals over 15 years of age [2]. Only 2 sera (1.3%) were positive for HBsAg [2]. These 2 sera were negative for anti-HBc antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, comparable population-level data on the impact of universal infant vaccination is not available for countries in this region, but several studies have demonstrated a reduction in HBV infection following vaccination with recombinant vaccines in Peru [45], Venezuela [46] and Brazil [47]. Moreover, a recent analysis of the a determinant of HBsAg in 21 Chilean patients chronically infected with HBV genotype F revealed that none of their isolates contained changes that would affect binding to vaccination-associated anti-HBs [48].…”
Section: Impact Of Hepatitis B Vaccinationmentioning
confidence: 99%